Phenotypic and transcriptomic changes in the corneal epithelium following exposure to cigarette smoke. (15th October 2021) - Jin, Mengyi; Wang, Yanzi; An, Xiaoya; Kang, Honghua; Wang, Yixin; Wang, Guoliang; Gao, Yang; Wu, Shuiping; Reinach, Peter S.; Liu, Zuguo; Xue, Yuhua; Li, Cheng
Abstract: Cigarette smoke extract (CSE), a complex mixture of compounds, contributes to a range of eye diseases; however, the underlying pathophysiological responses to tobacco smoke remain ambiguous. The purpose of the present study was to evaluate the cigarette smoke-induced phenotypic and transcriptomic changes in the corneal epithelium with a view to elucidating the likely underlying mechanism. Accordingly, for the first time, we characterized the genome-wide effects of CSE on the corneal epithelium. The ocular surface of the mice in the experimental groups was exposed to CSE for 1 h per day for a period of one week, while mice in the control group were exposed to preservative-free artificial tears. Corneal fluorescein staining, in vivo confocal microscopy and scanning electron microscopy were performed to examine the corneal ultrastructure. Transcriptome sequencing and bioinformatics analysis were performed followed by RT-qPCR to validate gene expression changes. The results indicate that CSE exposure disrupted the structural integrity of the superficial epithelium, decreased the density of microvilli, and compromised the corneal epithelial barrier intactness. RNA-seq revealed 667 differentially expressed genes, and functional analysis highlighted the enhancement of several biological processes such as antioxidant activity and the response to oxidative stress. Moreover, the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis showed that glutathione metabolism and drug metabolism cytochrome P450 were the most relevant pathways contributing to the effects of CSE on the corneal epithelium. Protein–protein interaction (PPI) network analysis illustrated that GCLC, NQO1, and HMOX1 were the most relevant nodes. In conclusion, the present study indicates that CSE exposure induces changes in the phenotype and genotype of the corneal epithelium. The antioxidant response element is essential for counteracting the effects of cigarette smoke on this tissue layer. These results shed novel insights into how cigarette smoke damages this ocular surface. Graphical abstract: Image 1 Highlights: We established a novel method that could qualitatively and quantitatively characterize alterations in vivo induced by CSE. CSE destroyed the structure and barrier function of the corneal epithelium in mice in a dose-dependent manner. CSE activated glutathione metabolism and cytochrome P450-mediated metabolism of xenobiotics in corneal epithelium. CSE enhanced the antioxidant activity of corneal epithelium by upregulating antioxidant-related genes. Abstract : Exposure of the corneal epithelium to cigarette smoke altered the phenotypic and genotypic characteristics which compromised its effectiveness at preserving normal vision.